THE ANALYSIS OF TEACHERS' STRATEGIES IN TEACHING READING AT SMAN 1 PRINGGARATA IN ACADEMIC YEAR 2022/2023 - Maesri Latipah; Lalu Thohir; Agus Saputra (Program Studi Pendidikan Bahasa Inggris, 2023)
There are still many obstacles to comprehending the reading text faced by the students. Thus, the implementation of teacher strategies in teaching reading is needed. The main problem that teachers faced was that sometimes the students got high scores but did not truly understand how the reading was supposed to be done. Thus, in these cases, the learning process did not run effectively. The researcher selected a descriptive qualitative research as the research design. The purposes of the research to find out the types of strategies used in teaching reading, to explain the reasons of teachers use those strategies and to find out the mostly strategy used in teaching reading. The subjects of this research are three English teachers at SMAN 1 Pringgarata. This research showed that, there were four types of teachers’ strategies; Scaffolding, think-aloud, reciprocal, and QARs. The main reasons of teachers used those four types of strategies such as to guide and assist students in an appropriate reading process, to make students be critical in receiving more important information, to make create an effective learning process and to stimulate students in responding the questions by the teachers. Finally, in accordance to the previous explanations, the scaffolding was the strategy mostly used by the teachers at SMAN 1 Pringgarata.